COVID-19 preventive behavior and associated factors in nursing students - Ana Paula Faria Cortes; Vanessa Faria Cortes; Olga Luisa Lucena; Cezenário Gonçalves Campos; Thalyta Cristina Mansano Schlosser; Alba Otoni; Rafael Gonçalves Teixeira Neto; Márcia Christina Caetano Romano (Revista Gaúcha de Enfermagem)
ABSTRACT Objective: To evaluate COVID-19 preventive behavior and associated factors in nursing students. Methods: Cross-sectional study carried out between March and October 2023, involving 126 nursing graduates. An instrument was applied to assess the knowledge, behaviors, symptoms, and vaccination status in regard to COVID-19. COVID-19 tests were carried out to detect IgG/IgM antibodies, as well as RT-PCR. Descriptive and multivariate analyses were performed. Results: 54.8% of participants reported they followed the recommendations for preventing and controlling the spread of COVID-19 and 10.3% said they used masks in crowded situations in open spaces, while 41.3% said they did so in closed places. All participants obtained reactive results for antibodies against COVID-19 and reported being vaccinated, with no cases of active infection. Factors associated with adequate preventive behaviors include self-declared black skin color and the use of masks when in crowds. Conclusion: This study found self-care indicators that may contribute to the development of public policies for disease prevention and health promotion in the university environment.